Die Bauchronologie und das Raumprogramm der Deutchordensburg Barten (Barciany) im Lichte Mittelalterlicher Schriftquellen - Jóźwiak, Sławomir; Trupinda, Janusz (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2018)
The chronology of construction and floor plan of the Teutonic Order’s castle in Barten (Barciany) in the light of medieval written sources The first wood-and-earth stronghold in Barten (Barciany) (its exact location is unknown) was constructed in 1325. In the late 1340s the stronghold was the seat of vogt, and in the early 1350s – a Teutonic Order’s procurator (pfleger) subject to the authority of the Brandenburg commanders. The construction of a brick castle in Barten was initiated in 1377. From the very beginning it was planned to be a regular four-sided stronghold with at least three wings of representative, residential and economic role. The intensive work on its construction was carried out during 1383 and 1384. The east wing – the main one – was finished by 1387, while the construction of the north wing was still in progress and lasted probably until 1395, undoubtedly as a result of the promotion of Barten to the rank of the commander’s convent (in 1394-1395). Despite this, the north wing never reached the planned height, and the construction of the other two was not even begun in the Middle Ages. Perhaps also in the mid-1390s the building of outer bailey was launched on the east side of the castle (nothing is known about its appearance). From1396 the Barten castle once again became the seat of a Teutonic Order’s procurators, who, depending on the administrative reforms carried out at that time in this part of the Teutonic Order’s State, were subordinate to either Rhein or Brandenburg commanders. The round tower, the only one that exists today, was probably erected only after 1410.